The trouble with cowboys ebook - Cutler, Melissa (Catcher Creek., 2012)
It was their parents' ranch, through the good days and the bad. But if they want to hang on to their land, their pride, and their family, the three Sorentino sisters will have to reinvent it from the ground up—and one of them just may reinvent herself in the process. . . Cowboys have never been good for Amy Sorentino. First her hard-riding father bankrupted the family farm. Then her all-hat-no-cattle boyfriend sold her out on national television, ending her promising career as a chef. Now she and her squabbling sisters have partnered up in a final attempt to save their land by starting an inn and local restaurant. So it figures that with everything on the line, Amy's key supplier is just the kind of Stetson-tipping heartbreaking bad boy she's sworn to avoid. But Kellan Reed has a few secrets of his own—and cowboy or not, Amy can't resist this kind of wild ride. . . "One hot romance from start to finish." —Carolyn Brown, New York Times bestselling author of Mistletoe Cowboy "Simply delightful."— New York Times bestselling author Lori Wilde